BIOLOGICAL SYNTHESIS OF NANOPARTICLES FROM MEDICINAL PLANTS AND ITS USES IN INHIBITING BIOFILM FORMATION - Agarwal, Harshita; MAHALINGAM GAYATHRI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Pathogenic micro-organisms have become the main problem in today's world. All microbes are getting resistant to antibiotics. This is due to the formation of biofilm layer above the micro-organisms. Learning the characteristics of biofilm can help us in treating the infectious disease induced via micro-organisms. They affect human's life in some or the other way. For example, the plaque formed in our teeth that cause tooth decay is due to the bacterial biofilm. When micro-organisms stick to moist or wet surfaces, it produces glue-like, slimy contents which are known as biofilms. Biofilms belong to the sessile communities, communities in which organisms are considered as immobile. Biofilms are enclosed within a matrix, known as extracellular polymeric matrix, which are secreted by micro-organisms. Biofilms attached to the surfaces are affected by certain characteristics like the growth medium, substratum to which it is attached and cellular surfaces. Each of these factors can either increase or decrease the hold of biofilm on the surfaces. With the help of biofilms, micro-organisms protect themselves from antibiotics and cause various infectious disease. Recent studies had proved medicinal plants to be effective in treating disease caused by microbes. Medicinal plants produce active compounds during secondary metabolism which help in the treatment of infectious disease. The problem that arises with antibiotics is that they are unable to penetrate through the biofilm. This problem is solved by converting antibiotics in nanoparticle size. Nanoparticles have high penetrating ability than the antibiotics. They help in controlling microbial growth by killing them. Â 